2012
DOI: 10.1523/jneurosci.3069-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Determinants of Light Sensitivity in Amphioxus Microvillar Photoreceptors: Possible Evolutionary Implications for Melanopsin Signaling

Abstract: Melanopsin, a photopigment related to the rhodopsin of microvillar photoreceptors of invertebrates, evolved in vertebrates to subserve nonvisual light-sensing functions, such as the pupillary reflex and entrainment of circadian rhythms. However, vertebrate circadian receptors display no hint of a microvillar specialization and show an extremely low light sensitivity and sluggish kinetics. Recently in amphioxus, the most basal chordate, melanopsin-expressing photoreceptors were characterized; these cells share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…3D). Consistent with the above hypothesis, amphioxus Hesse and Joseph photoreceptor cells, in which the melanopsin functions as a photopigment (16), show a high photosensitivity comparable to visual photoreceptor cells (65), in contrast to ipRGCs in mammals.…”
Section: Dog Opn4supporting
confidence: 74%
“…3D). Consistent with the above hypothesis, amphioxus Hesse and Joseph photoreceptor cells, in which the melanopsin functions as a photopigment (16), show a high photosensitivity comparable to visual photoreceptor cells (65), in contrast to ipRGCs in mammals.…”
Section: Dog Opn4supporting
confidence: 74%
“…The physiology and phototransduction cascade in isolated DO and JCs has been investigated in several studies (Acemel et al, 2016;Angueyra et al, 2012;Ferrer et al, 2012;Gomez Mdel et al, 2009;Nasi and del Pilar Gomez, 2009;Peinado et al, 2015;Pulido et al, 2012). These seminal studies not only confirmed that JCs and DO indeed function as photoreceptors, but also provided comparative data with respect to invertebrate rhabdomeric photoreceptors and ipRGCs.…”
Section: Rhabdomeric Photoreceptorsmentioning
confidence: 96%
“…The different studies carried out so far on melanopsin light sensitivity do not lead to consistent results. Although Do et al (14) argue that ipRGCs work at extremely low irradiation intensities showing a single-photon response larger than rods, Ferrer et al (15) conclude that the melanopsin has a reduced sensitivity relative to visual pigments. On the other hand, these photoreceptors would be expected to display high light sensitivity (14).…”
mentioning
confidence: 99%